P‐88: Transparent Quantum Dot Light‐Emitting Diodes with Sputtered ITO Electrodes. Issue 1 (May 2016) - Wang, Weigao; Chen, Shuming
Abstract : Transparent, all‐solution processed quantum‐dot light‐emitting diodes (QD‐LEDs) are developed in this work. Indium‐tin‐oxide (ITO) fabricated by sputtering is adopted as transparent electrodes for the QD‐LEDs. To reduce the plasma damage caused by the sputtering, ZnO nanocrystals with thickness of 82 nm are employed as buffer layer and electron transport layer. As a result, damage‐free QD‐LEDs are demonstrated with high averaged transparency of 70%. The transparent QD‐LEDs exhibit external quantum efficiency of 5% (current efficiency of 7 cd/A), which is comparable to that of the devices with conventional Al electrodes.